Outcomes Associated With ABCG2 and CD133 Expression in Patients With Gastric Cancer After Surgical Resection - Donghoon Kang; Jae Myung Park; Sung Hak Lee; Yu Kyung Cho; Bo-In Lee; Myung-Gyu Choi (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Objectives Adenosine triphosphate-binding cassette subfamily G member 2 (ABCG2) and CD133 are recognized stem cell markers of gastric cancer. Extensive research has examined the significance of these markers in different types of cancers and their impact on prognoses, linking them to unfavorable clinical outcomes in various tumors. However, the prognostic value of these markers for gastric cancer remains unclear. We investigated the expression of ABCG2 and CD133 and their relationship with clinical outcomes in gastric cancer. Methods ABCG2 and CD133 expression levels were analyzed, using immunohistochemistry and tissue microarrays, in tumor samples from 459 patients who underwent surgical resections due to gastric cancer. ABCG2 and CD133 expression levels were defined by intensity and dichotomized as medians. The associations among the expression levels of these markers, disease severity, and patient survival were also determined. Results In the 411 patients for whom we analyzed the expression levels of these markers, 74.9% and 80.5% were found to have high levels of ABCG2 and CD133, respectively. High expression levels of ABCG2 and CD133 were more commonly observed in well-differentiated (p<0.001 and p=0.004, respectively) and intestinal lesions (p<0.001 and p=0.002, respectively). High ABCG2 expression correlated with improved survival outcomes, whereas high CD133 expression was associated with poorer outcomes. Cox regression analysis confirmed that stage, high ABCG2 (overall survival [OS]: hazard ratio [HR], 0.61; 95% confidence interval [CI], 0.41–0.91; p=0.015; recurrencefree survival [RFS]: HR, 0.55; 95% CI, 0.34–0.88; p=0.012), and CD133 expression (OS: HR, 1.59; 95% CI, 1.00–2.51; p=0.049; RFS: HR, 2.29; 95% CI, 1.21–4.34; p=0.011) were predictors of survival. A subgroup analysis indicated that ABCG2 expression was also associated with an improved RFS rate in patients who received systemic chemotherapy. Conclusions High ABCG2 expression and low CD133 expression in tumors correlated with improved survival outcomes in post-resection patients with gastric cancer, suggesting their potential utility as prognostic biomarkers.